A Lower Cretaceous Lagerstätte from France: a taphonomic overview of the Angeac‐Charente vertebrate assemblage. (23rd January 2021) - Rozada, Lee; Allain, Ronan; Vullo, Romain; Goedert, Jean; Augier, Dominique; Jean, Amandine; Marchal, Jonathan; Peyre de Fabrègues, Claire; Qvarnström, Martin; Royo‐Torres, Rafael
Abstract : Terrestrial ecosystems from the Lower Cretaceous of Europe and bonebeds formed in swampy environments are poorly known. The Berriasian‐early Valanginian Angeac‐Charente site in France represents an example of both. Nine field campaigns have yielded thousands of fossils of over a hundred taxa, including 16 taxa from vertebrate macroremains with numerous trample and crocodile bite marks; 22 taxa from the abundant vertebrate microremains; >10 vertebrate coprolite morphotypes with plant and vertebrate inclusions; abundant sauropod and stegosaur tracks including some preserved in '4‐D'; termite coprolites; mollusc moulds; ostracods and plants, including coniferous wood, cones, leaves and cuticle fragments, charophytes and pollen. The richness, diversity and preservation of the fossils qualify the site as a fossil‐Lagerstätte . The site represents a 'snapshot' into a Lower Cretaceous ecosystem. This is supported by REE analyses of biogenic apatite and sediment samples, the fossils being found in a single stratigraphical interval and the record of sedimentological and taphonomic 'frozen scenes'. The Angeac‐Charente bonebed is highly diverse, dominated by an ornithomimosaur taxon, and contains both macro‐ and microfossils. This indicates a complex formation, likely primarily influenced by ecological and biologic processes, but also significant physical processes. These include crocodyliform predation and/or scavenging on turtles, ornithomimosaurs and fishes; probable mass mortality occurrence of an ornithomimosaur herd; possible social behaviour of stegosaurs; limited hydraulic transport of most sauropod bones and intense dinoturbation.